Industrial Training Report: Perbadanan Perpustakaan Awam Negeri Sembilan (PPANS) / Hazwani Othman - Othman, Hazwani (Faculty of Information Management, 2018)
The 5 months practical training that I undergo at Perbadanan Perpustakaan Awam Negeri Sembilan (PPANS), Iis excellent as I am able to finish is accordingly as required by Faculty of lnfonnation Management for the course Bachelor of Info1mation Science (Hons.) Library Management for about 20 weeks stat1ing from early of August 2018 until end of Dicember 2018. I am exposed to many new things which are very valuable for me to learn and carry out with devotion when I face the real word of working in the future. This report book is an overall activity throughout the process of industrial training that contains industry training information, beliefs and conclusions of the whole report, and comments related to the training being unde11aken as well as suggestions for organizations for future improvement process. Overall, the rep011 is presented to the academic supervisor, Sir Ridzuaan bin Ibrahim, from faculty of Information Management to evaluate and understand every work that has been done by the student while undergoing industry training in the organization. The world of working is a completely different phase compared to studying world: therefor by going for an industrial training, I hope that the students are well prepared and have high confidence to serve the community. I will strive to use gained skills and knowledge in the best possible way.